Aktivitas Antibakteri Ekstrak Daun Kapuk Randu (Ceiba Petandra (L.) Gaertn) terhadap Isolat Bakteri Pseudomonas Aeruginosa Asal Infeksi Luka Operasi - Mulia Susanti; Fina Wahyu Utami (Akademi Analis Kesehatan Pekalongan, 2024)
Surgical wound infection (SSI) is an infection that occurs in surgical incision wounds. Complications in surgical incision wounds often occur due to tissue cessation so that there is a gap for microorganisms to enter. Pseudomonas aeruginosa is one of the microorganisms that causes the most infections in surgical wounds. To avoid and suppress infection, antibiotics play a role in reducing morbidity and mortality. However, inappropriate use of antibiotics can increase bacterial resistance. Indonesia is a country with natural resources that are widely used in traditional medicine. One of them is the use of Kapok Randu leaves (Ceiba petandra (L.) Gaertn). Kapok Randu leaves contain antibacterial compounds such as flavonoids, alkaloids, saponins and tannins. This study aims to determine the minimum concentration of Kapok Randu leaf extract (Ceiba petandra (L.) Gaertn) as an antibacterial against Pseudomonas aeruginosa bacterial isolates originating from surgical wound infections. This study is an experimental study, using the well method to test the killing power of ethanol extract of kapok randu leaves against Pseudomonas aeruginosa isolates. The results of the antibacterial power test of kapok randu leaf extract found that at concentrations of 10%, 30% and 50% there was no suicide zone, while at concentrations of 70%, 90% and 100% a suicide zone was formed with a diameter of 9 mm, 10 mm and 12 mm. it can be concluded that the minimum bactericidal content (MBC) of Kapok Randu leaf extract (Ceiba Petandra (L.) Gaertn) against Pseudomonas aeruginosa bacteria at a concentration of 70% with a diameter of 9 mm.